PENGGUNAAN MEDIA PREZI UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SENI RUPA DI KELAS XI IPS 1 SMA ADABIAH PADANG - Putri Tri Syafna, Drs. Suib Awrus, M.Pd. (Serupa The Journal of Art Education, 2019)
This study aims to improve motivation and learning outcomes by using prezi media as medium for learning art in the XI IPS 1 class at Adabiah Padang High School. The research method used is classroom action research. The research instrument is a test of student learning outcomes, student motivation questionnaire, teacher activity observation sheet, observation sheet of student activity. The results of the study stated that 1) the use of prezi media can increase the motivation of students in learning art in the XI IPS 1 class at Adabiah Padang High School. 2) the use of prezi media can improve student learning outcomes in learning at in class XI IPS 1 Adabiah High School Padang.Keywords: Media Prezi, significant learning outcomes